2013
DOI: 10.1089/vbz.2011.0916
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Attitude Toward Zoonoses with Particular Reference to Anthrax Among Cattle Owners in Selected Rural Communities of Zimbabwe

Abstract: We conducted a cross-sectional study to assess cattle owners' awareness, perceptions, and attitudes toward zoonoses, with particular emphasis regarding anthrax. Data on awareness of zoonoses, clinical signs of anthrax in animals and human, its routes of transmission and methods of prevention, the families' consumption habits of anthrax-infected carcasses, and other family activities that increase exposure to anthrax were collected using an interviewer-administered questionnaire. A total of 41.4% (135/326) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 27 publications
5
28
0
Order By: Relevance
“…Only 25.4% of the farmers utilized appropriate anthrax prevention practices in the district. Studies conducted to assess anthrax prevention practices among livestock owners in Turkey and Zimbabwe indicated that 51.9% [13] and 86% [3], of the owners appropriately managed the disease, respectively. Compared to these findings, the result of this work was lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 25.4% of the farmers utilized appropriate anthrax prevention practices in the district. Studies conducted to assess anthrax prevention practices among livestock owners in Turkey and Zimbabwe indicated that 51.9% [13] and 86% [3], of the owners appropriately managed the disease, respectively. Compared to these findings, the result of this work was lower.…”
Section: Discussionmentioning
confidence: 99%
“…Anthrax is a zoonotic bacterial disease caused by Bacillus anthracis [1].When B. antharcis are exposed to air, they rapidly sporulate to form very persistent spores [2]. The spores (i.e., dormant stage) are resistant to heat and chemical disinfectants and may persist and remain viable in soil for several decades [2,3]. Herbivorous and wild mammals are the most commonly affected groups through the ingestion or inhalation of spores while grazing.…”
Section: Introductionmentioning
confidence: 99%
“…Hundal et al, (2016) revealed in his cross sectional study, their herd size up to 10 animals (79.6 %). Tebug (2013) Chikerema et al, (2013) found that awareness amongst the farmers was known viz., Rabies (88.7 %), Anthrax (71.5%) and Brucellosis (20.9 %). Tesfaye et al, (2013) revealed that were rabies (97.1 %), followed by Taeniasis (83.4 %), anthrax (55.4 %), Bovine tuberculosis (29.1 %) and Hydatidosis (4 %) knew on common zoonotic diseases.…”
Section: Number Of Animal Experience and System Of Rearingmentioning
confidence: 99%
“…According to (Chenyambuga et al, 2010) the currently held concept of TBDs control has to be revised and should consider the indigenous knowledge of livestock keepers. Literature search on the involvement of farmers in studying the epidemiology of diseases in Zimbabwe revealed that only a few studies had been conducted (Chikerema et al, 2013;De Garine-Wichatitsky et al, 2013;Mosalagae et al, 2011;Pfukenyi et al, 2010) and none of these have directly looked at TBDs. This is despite the importance placed on TBDs by the government Department of Veterinary Services in the country.…”
Section: Introductionmentioning
confidence: 99%